Modelling and forecasting spatio-temporal variation in the risk of chronic malnutrition among under-five children in Ghana. (June 2017) - Aheto, Justice Moses K.; Taylor, Benjamin M.; Keegan, Thomas J.; Diggle, Peter J.
Highlights: This is the first study to explore spatio-temporal patterns in < 5 stunting. We develop a spatio-temporal model to capture variation in childhood stunting. Our method facilitates and enriches modelling and forecasting of future stunting. Substantial spatio-temporal variation exists in the risk of under 5 child stunting. Our method allows identification of higher risk communities for policy decisions. Abstract: Background: Spatio-temporal variation in under-5-year-old children malnutrition remains unstudied in most developing countries like Ghana. This study explores and forecasts the spatio-temporal patterns in childhood chronic malnutrition among these children. We also investigate the effect of maternal education on childhood malnutrition. Methods: We analysed data on 10, 036 children residing in 1516 geographic locations. A spatio-temporal model was fitted to the data and was used to produce predictive maps of spatio-temporal variation in the probability of stunting. Results: The study found substantial spatio-temporal variation in the prevalence of stunting. Also, higher levels of mother's education were associated with decreased risk of being stunted. Conclusion: Our spatio-temporal model captured variations in childhood stunting over place and time. Our method facilitates and enriches modelling and forecasting of future stunting prevalence to identify areas at high risk. Improving maternal education could be given greater consideration within an overall strategy for addressing childhood malnutrition.